Efficacy of indigenous strains of entomopathogenic nematodes, Steinernema feltiae and Heterorhabditis bacteriophora against the white grub, Brahmina coriacea - Sharma, Isha; Singh, Mohinder; Sharma, P L (Indian Journal of Plant Protection, 2020)
The studies were conducted to evaluate the potential of two indigenous strains of entomopathogenic nematodes (EPN), Heterorhabditis bacteriophora and Steinernema feltiae against the white grub, Brahmina coriacea. Both the EPN species were found highly effective against 2nd and 3rd instar grubs of B. coriacea. S. feltiae was found slightly better than H. bacteriophora against the 2nd instar grubs with average mortality of 45.00 to 83.89 per cent against 39.44 to 82.22 per cent average mortality in H. bacteriophora at different concentrations in 30 days of exposure to nematodes. The LC50 values for S. feltiae at 10 and 15 days after treatment against the2nd instar grubs were 39.84 and 12.37 IJs/cm2, respectively, and 71.45 and 20.59 IJs/cm2 in H. bacteriophora at same exposure period. Similarly, LT50 values for S. feltiae against 2nd instar grubs were 11.4 days and 9.2 days at concentrations of 20 and 40 IJs/cm2, respectively, whereas, for H. bacteriophora, the LT50 values of 14.7 and 11.3 days were obtained at same concentrations. H. bacteriophora was proved better than S. feltiae against 3rd instar grubs with 100 per cent morality with this species at 160 IJs/cm2 after 25 days of treatment against 80.00 per cent mortality with S. feltiae at same concentration and exposure period. The LC50 value of H. bacteriophora against 3rd instar grub at 20 days after treatment was found to be 18.33 IJs/cm2 whereas 29.26 IJs/cm2 for S. feltiae. The LT50 values of H. bacteriophora against 3rd instar at 40 and 80 IJs/cm2 were 15.8 and 9.7 days, respectively and 16.7 and 13.9 days in S. feltiae at same concentrations. These nematodes have potential biocontrol agents against white grub, B. coriacea.